Numerical Model For Tsunami Propagation Due To A Time Dependent Source Along Peninsular Malaysia And Southern Thailand - Ishak, Umi Hazirah (2010)
The event of the 26th December 2004 Sumatra-Andaman Earthquake was very profound in its impact since it generated a widespread tsunami throughout the Indian Ocean rim countries. The west coast of Peninsular Malaysia and the coast of southern Thailand were also attacked by the massive tsunami waves thus proving that these two affected regions are also in a vulnerable position for tsunami surge due to a permanent source in Sumatra, Indonesia. Ever since the devastating event, lots of studies and researches had been done by various researchers from all over the world in order to better understand the phenomenon. Kowalik et al. (2005) and Roy and Ismail (2005). These researchers considered an instantaneous sea surface uplift and subsidence along the whole source zone which was caused by an abrupt slip at the India / Burma plate interface and that was assigned as the initial condition. But, the rupture of the sea surface elevation along the fault line spreads over 1300km long and it propagated for about 8 minutes (Ishii et al., 2005). Ammon et al. (2005) also indicated that the rupture propagated approximately 1200km of the ruptured fault length in about 500 seconds. Thus, by considering these facts, the initial disturbance of the sea surface along the whole source zone is time dependent.